2023
DOI: 10.1101/2023.07.20.549878
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dermonecrosis caused by spitting cobra snakebite results from toxin potentiation and is prevented by the repurposed drug varespladib

Abstract: Snakebite envenoming is a neglected tropical disease that causes substantial mortality and morbidity globally. The venom of African spitting cobras often causes permanent injury via tissue-destructive dermonecrosis at the bite site, which is ineffectively treated by current antivenoms. To address this therapeutic gap, we identified the aetiological venom toxins responsible for causing local dermonecrosis. While cytotoxic three-finger toxins were primarily responsible for causing spitting cobra cytotoxicity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
(144 reference statements)
0
2
0
Order By: Relevance
“…Similarly, pre-incubation of the cytotoxin binder with isolated cytotoxin from N. pallida (2 IC 50 s) at a 1:5 molar ratio (toxin:binder) gave 85% protection against cytotoxicity (Figure 4c). However, preliminary studies indicated that the CYTX design, in 1:1, 1:2.5, and 1:5 molar ratios (toxin:binder), did not significantly decrease the size of the dermonecrotic lesions induced by intradermal N. nigricollis venom administration in a murine model 55 (Supplementary Fig. S7); the affinity of CYTX likely needs to be further optimized for full in vivo neutralization of cytotoxins.…”
Section: In Vitro Neutralizationmentioning
confidence: 99%
“…Similarly, pre-incubation of the cytotoxin binder with isolated cytotoxin from N. pallida (2 IC 50 s) at a 1:5 molar ratio (toxin:binder) gave 85% protection against cytotoxicity (Figure 4c). However, preliminary studies indicated that the CYTX design, in 1:1, 1:2.5, and 1:5 molar ratios (toxin:binder), did not significantly decrease the size of the dermonecrotic lesions induced by intradermal N. nigricollis venom administration in a murine model 55 (Supplementary Fig. S7); the affinity of CYTX likely needs to be further optimized for full in vivo neutralization of cytotoxins.…”
Section: In Vitro Neutralizationmentioning
confidence: 99%
“…60 However, care must be taken in this approach, as recent research has suggested that cell culture models do not accurately recapitulate dermonecrosis. 96 Daboia spp. venoms: The pathophysiology of envenomings by Daboia spp.…”
Section: Rescue Modelsmentioning
confidence: 99%